A sprouting graph-based approach to analysing timed workflow processes with shared resources. (2017) - Du, Yanhua; Li, Ruyue; Yang, Benyuan
Recently, temporal constraint satisfiability is regarded as an important criterion in the field of business process management. Existing methods do not fully investigate the various modes of shared resources, cannot provide the solutions for temporal violations or cannot develop the prototype system to automatically verify them. In this paper, we propose a new sprouting graph based approach to analysing temporal constraints of workflow processes with shared resources. First of all, in order to deal with various modes of shared resources we propose the corresponding patterns to record the executing information of resources. Then, how to automatically construct sprouting graph is presented, and the procedure of solving temporal violations is proposed. Finally, we also develop a prototype system. Compared with existing works, our approach is more effective and practical in the real business environment.